Effect of edible wax coating and modified atmospheric packaging on shelf life of slicing cucumber (Cucumis sativus) - CHINCHU MOHAN HIMA JOHN; Dr. Sudheer K.P (Guide) (Tavanur 2013 Department of Post-Harvest Technology and Agricultural Processing)
Effect of edible wax coating and modified atmospheric packaging on shelf life of slicing cucumber (Cucumis sativus)
Effect of edible wax coating and modified atmospheric packaging on shelf life of slicing cucumber (Cucumis sativus)